Synthesis of functionalized tryptamines by Brønsted acid catalysed cascade reactions. Issue 83 (3rd September 2015) - Melis, Nicola; Secci, Francesco; Boddaert, Thomas; Aitken, David J.; Frongia, Angelo
Abstract : A new solvent-free Brønsted acid catalysed cascade reaction has been established, allowing access to highly substituted tryptamines under mild conditions. Abstract : An original synthetic protocol has been developed for the preparation of highly functionalized tryptamines from 2-hydroxycyclobutanone and secondary arylamines via a solvent-free Brønsted acid catalysed two-step reaction sequence.